WAD - Criteria for Evaluation of Causality - Olle Bunketorp (Open Journal of Trauma - Peertechz Publications, 2017)
Whiplash Associated Disorders (WAD) have caused frustrating problems since decades for people injured in various types of accidents. Certain circumstances and misunderstandings explain this anomaly. They often become obvious (some as paradoxes) when it comes to estimation of crash severity, biomechanics, injury tolerance, diagnostic procedures, pain physiology, follow-up procedures and injury compensation. This presentation aims to describe some of them, especially with regard to the question of causality, i.e. if it is right to claim that an individual´s posttraumatic problems are caused by a traumatic event or not. There are well-defined criteria, which should be used to assess whether there is a causal link between a harmful event and a consequent disorder. They were presented by Sir Austin Bradford Hill, already in 1965 [1]. There have been several discussions on their validity since then [2]. Freeman et al., made a thorough review of the literature regarding these items in 2008 and 2009 [3,4]. The second paper gave specific reference to symptomatic spinal disk injury following motor vehicle trauma.